Factorial screening of ferulic acid production from fiber pressed oil palm frond using mixed culture - Nurul Atikah, Mohd Rodzri (2015)
Ferulic acid (FA) belongs to the family of phenolic acid and is abundantly found in vegetables and fruits. It is one of the organic compound antioxidant and is extensively used in many industries due to its properties such as anti-inflammatory, antimicrobial and anti-carcinogenic. FPOPF is a renewable substrate and abundantly available in Malaysia therefore it was used as the substrate for the production of FA. Mixed culture was used instead of single culture and co-culture because of its ability to facilitate biological process under non-sterile condition. The fractional factorial screening experiments were performed for parameters of inital pH value, incubation temperature, fermentation time, agitation rate and substrate-to-inoculum ratio. The purpose of the fractional factorial screening was to determine the effect of those independent parameters on the production of FA from FPOPF using mixed culture. There were a total of 16 runs of experiments performed and the most contributing parameters to FA production from FPOPF were determined using Design Expert software. The ANOVA indicated that the model was significant with a coefficient of determination value of 0.8978. Temperature and pH value provided two of the highest contribution to the process. There were two factor interactions discovered throughout the process, interaction between factor A, temperature and factor B, pH value; and interaction between factor A, temperature and factor C, agitation.